A Structural Equation Model of Writing Anxiety, Writing Motivation and Academic Motivation of Students - Deniz, Hacer; Demir, Sezgin (My University, 2024)
Writing anxiety causes various problems in the writing process, makes it difficult for the person to produce text and can prevent the act of writing. Writing motivation supports writing skills by affecting the writing process positively. The purpose of this research is to determine relationships between students' writing anxiety, writing motivation and academic motivation. The research was carried out with the correlational desing in the quantitative method. The population of this research consist of secondary school students and the sample consist of 1037 secondary school students, 577 of whom are females (55.64%) and 460 of them are males (44.36%) in Elazig province centre in 2020-2021 academic year. As a result of the correlation test, hierarchical regression analysis, it was determined that students' writing anxiety meaningful was predicted the writing motivation (r=-.65/strong) and academic motivations (r=-.37/medium) by 53%. Structural equation model fit was verified. While writing process, avoidance and writing pleasure latent variables explain 11% of consubstantiated extrinsic motivation, this rate increased to 45% when writing motivation was added to the equality. Although writing process, avoidance and writing pleasure variables explained 39% of the unmotivation and 32% of the extrinsic motivation reflected internal, it was observed that the regression coefficient for the two equations increased to 70% with the addition of writing motivation as the predictive variable.
Keywords: Writing anxiety; writing education; academic motivation; writing motivation; intrinsic and extrinsic motivation